Hall Effect Study of the Metamagnetic Transition in the Sr4(Ru0.99Fe0.01)3O10 Nanosheet - Wan, Jiajie; Liu, Yan; Wan, Yuanqing; Wu, Qing; Wang, Yu; Yang, Jiyong; Mao, Zhiqiang; Wang, Junzhong (Frontiers in Materials, 2022)
Sr4(Ru0.99Fe0.01)3O10 shows a ferromagnetic (FM) transition at TC~105 K with the magnetic easy axis in the ab plane, followed by a metamagnetic transition (MMT) at low temperatures when the magnetic field H is applied along the c axis, which is in sharp contrast to that of the pure Sr4Ru3O10, where the easy axis is along the c axis and the MMT is in the ab plane. Here, we studied the MMT in the Sr4(Ru0.99Fe0.01)3O10 nanosheet by Hall effect. It was found that the ordinary Hall coefficient of Sr4(Ru0.99Fe0.01)3O10 is almost the same as that of the pure Sr4Ru3O10, while a sudden increase in the Hall resistance Rxy is observed below ~50 K. Above which, the Rxy presents the conventional anomalous Hall effect up to TC. Analysis of the results indicate that the MMT has no direct correlation to the electronic structure, but closely relates to the magnetic moments locking, where the magnetic field induced breakdown of the locked moments is responsible for the MMT.